A model for the development of high quality training of tourism professionals through the use of computer 3D-tours - Lepky, Mykhailo I.; Matviichuk, Liudmyla Y.; Lysiuk, Tetiana V.; Tereshchuk, Oksana S.; Podolak, Volodymyr M. (Journal of Geology, Geography and Geoecology, 2020)
The article is focused on the problem of training future tourism specialists using informational and communication technologies. The educational process of preparation requires changing the educational and methodological support in order to give the students the opportunities to master modern professional tools, technologies, methods of creating high quality tourist products. To solve this problem, the authors propose a model for the development of high quality training of tourism professionals through the use of computer 3D-tours. The development of this model took into account the theoretical and methodological basis regarding the professional training of future specialists in the field of tourism, the results of the analysis of educational programs, curricula for training students of the speciality “Tourism” and the data of the pilot experiment. It consists of the following main blocks. The conceptual-oriented block includes concepts, approaches, principles of participation, information and communication technologies. The content-technological block includes the content of the educational project of developing 3D-tours, levels of professional knowledge and skills, as well as types of familiriazation with ICT tools. The educational content of the model takes into account the practical mastery of the student’s professional skills in the development of various 3D-tours. During this process, the ICT tools are introduced gradually in a certain order. The organization-activity block of the model includes forms of organizing the study and technologies for studying. This model entails the involvement of classroom-based and remote, individual, and group forms of organization of the educational process, organization of project development for a detailed analysis of educational topics. The assessment-resultative block includes criteria, metrics and levels. During the development of the model, the results of the activity of the subjects of the educational process were analyzed in accordance with two groups of criteria: the criterion of formation of professional theoretical knowledge, practical skills of 3D-tour development and the criterion of the level of using modern software and technical means in creative educational development. The developed model allows for increasing the quality of training of future tourism specialists. During the practical application of the proposed model, virtual 3D-tours were developed. Their development has shown the possibility of implementing the model of development of training of specialists in tourism by using computer 3D-tours with the use of modern ICT tools in the study of special disciplines and the attaining professional skills.
Keywords: virtual tour; tourism; development model; concepts; approaches; future specialists